Link between divertor conditions and high-field-side/low-field-side midplane density profiles in H-mode plasmas at ASDEX Upgrade. (18th October 2019) - Guimarais, L.; Silva, C.; Bernert, M.; Brida, D.; Cavedon, M.; Conway, G.D.; Drenik, A.; Gil, L.; Reichbauer, T.; Reimold, F.; Santos, J.; Seliunin, E.; et al.
Abstract: The connection between midplane and divertor conditions is studied on ASDEX Upgrade (AUG) for H-mode scenarios. H-mode discharges with variations in fuelling, heating power and impurity seeding are analysed, enabling to disentangle their impact on the evolution of midplane density profiles. The O-mode reflectometer installed on AUG provides unique insights on the midplane density profiles thanks to the ability to measure simultaneously at the high-field-side (HFS) and the low-field-side (LFS). At the inner divertor, with the onset of detachment, a region of high density is formed (HFS high density front, HFSHD) that expands into the HFS midplane, leading to strong poloidal asymmetries in the main chamber scrape-off layer (SOL) density. A good agreement is observed between the evolution of the density profiles at the midplane and that of the divertor volume density confirming the strong influence of divertor conditions on the midplane density profiles at the HFS. Our results confirm the existence of a relationship between plasma confinement, the shift in the midplane LFS density profile and the presence of the HFSHD with respect to changes in seeding and fuelling. It is established that the separatrix density at the LFS is better correlated with the neutral pressure at the outer target while the HFS SOL density follows the neutral pressure at the inner divertor. A comprehensive characterisation of the edge-localised mode (ELM) evolution at the midplane and divertor is performed demonstrating that also during the ELM cycle the divertor conditions have a strong effect on the SOL density at the midplane. The most striking result is the observation of a HFSHD at the HFS midplane just after the ELM crash associated with strong inner divertor detachment.